Edukasi Dan Skrining Sindrom Metabolik Berbasis Pemeriksaan Laboratorium Pada Masyarakat Berisiko Diabetes Melitus Di Desa Saentis, Kabupaten Deli Serdang: Pengabdian - Mutia, Liza; Pratiwi, Dian; Setiyawati, Dewi; Suparni; Wahyuni, Sri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The potential for solar energy in the Gunungkidul region, particularly in the Sidoharjo subdistrict, Gunungkidul, is abundant. The use of solar energy as an alternative energy source still needs to be continuously promoted. Public understanding of the use of solar energy to generate clean and sustainable electricity is still limited. The educational program is designed to provide knowledge about the use of solar energy as electricity. The objectives of the activities include increasing public literacy about Solar Power Plants (PLTS) that can be used as alternative energy. This activity focuses on delivering material on the basic principles of PLTS, its advantages as green energy that does not produce carbon emissions, and its economic benefits in saving long-term electricity costs. The methods used are participatory in nature, including socialization, workshops, and component demonstrations, which are tailored to the local context of Sidoharjo. The expected benefits and impacts of this program include the community's understanding of PLTS technology and the realization of public awareness of the importance of renewable energy. This program also aims to empower the community with practical knowledge so that they can take the initiative in utilizing solar energy.